Hydralazine Reverses Stress-Induced Elevations in Blood Pressure, Angiotensin II, Testosterone, and Coronary Pathology in a Social Colony Model. (20th July 2011) - Li, Changying; Salisbury, Ron; Ely, Daniel
Abstract : Background . The vasodilator hydralazine (HYZ) has been used successfully to lower blood pressure (BP) in hypertension. Recently proposed novel mechanisms suggest it may be an important drug in reducing cardiovascular pathology. Methods . The hypothesis was that social stress would increase BP and endocrine factors that lead to increased coronary artery collagen deposition, and that HYZ treatment would reverse these changes. SHR males were compared: controls, colony stress and colony stress with HYZ treatment. Results . BP was significantly elevated in the stress group compared to controls and HYZ reduced the BP compared to controls. Plasma Ang II and T were significantly increased by colony stress compared to controls and HYZ restored both to control values. Collagen deposition in the coronary artery was increased in the colony stress group compared to controls but HYZ treatment restored the collagen to that of control values. Conclusions . HYZ reduced not only BP, but also reduced coronary adventitial collagen. The mechanism of the BP effect is most likely through vasodilation and the collagen reduction may be due to both a direct action of HYZ on collagen synthetic enzymes and indirectly through an effect of testosterone and angiotensin II.